Phosphine-Mediated [3+2] Cyclization for the Synthesis of Coumarin-Based CF3-Containing Furanones - Gan, Wenhao; Fu, Junfeng; Zhou, Zhixiang; Cao, Sheng; Zhang, Zhipeng; Wang, Yongjiang; Han, Xiaoyu (Synlett, 2023)
A tertiary phosphine-mediated [3+2] cyclization reaction of ynones with fluorinated coumarin derivatives has been developed to give a series of coumarin-based CF3-containing furanones in moderate to good yields under mild reaction conditions. Preliminary investigation into their antitumor activities is also presented.
Keywords: phosphine; cyclization; coumarin; furanone